Oxazaphosphorines combined with immune checkpoint blockers: dose-dependent tuning between immune and cytotoxic effects. Issue 2 (11th August 2020) - Delahousse, Julia; Skarbek, Charles; Desbois, Mélanie; Perfettini, Jean-Luc; Chaput, Nathalie; Paci, Angelo
Abstract : Background: Oxazaphosphorines (cyclophosphamide (CPA), ifosfamide (IFO)) are major alkylating agents of polychemotherapy protocols but limiting their toxicity and increasing their efficacy could be of major interest. Oxazaphosphorines are prodrugs that require an activation by cytochrome P450 (CYP). CPA is mainly metabolized (>80%) to phosphoramide mustard while only 10%–50% of IFO is transformed in the alkylating entity, isophosphoramide mustard and 50%–90% of IFO release chloroacetaldehyde, a nephrotoxic and neurotoxic metabolite. Geranyloxy-IFO (G-IFO) was reported as a preactivated IFO to circumvent the toxic pathway giving directly the isophosphoramide mustard without CYP metabolization. The similarity in structure of CPA and IFO and the similarity in metabolic balance of CPA and G-IFO have led us to explore immunomodulatory effect of these components in mice and to investigate the combination of these oxazaphosphorines with immune checkpoint blockers (ICB). Methods: The investigation of the immunomodulatory properties of IFO and G-IFO compared with CPA has been conducted through immune cell phenotyping by flow cytometry and analysis of the cytokine profile of T cells after ex-vivo restimulation. T cell-mediated antitumor efficacy was confirmed in CD4 + and CD8 + T cell-depleted mice. A combination of oxazaphosphorines with an anti-programmed cell death 1 (PD-1) antibody has been studied in MCA205 tumor-bearing mice. Results: Studies on a MCA205 mouse model have demonstrated a dose-dependent effect of IFO and G-IFO on T cell immunity. These components in particular favored Th1 polarization when used at low dose (150 and eq. 100 mg/kg, respectively). Antitumor activity at low dose was abolished in mice depleted in CD4 + and CD8 + T cells. G-IFO at low dose (eq. 100 mg/kg) in combination with anti-PD-1 antidody showed high synergistic antitumor efficacy compared with IFO. Conclusion: Oxazaphosphorines are characterized by a dual mechanism of antitumor action; low-dose schedules should be preferred in combination with ICB, and dose escalation was found to have better utility in polychemotherapy protocols where a conventional direct cytotoxic anticancer effect is needed. G-IFO, the novel oxazaphosphorine drug, has shown a better metabolic index compared with IFO as its metabolization gives mainly the alkylating mustard as CPA (and not IFO) and a best potential in combination with ICB.